Effects of Phytochemically Characterized Extracts From Syringa vulgaris and Isolated Secoiridoids on Mediators of Inflammation in a Human Neutrophil Model - Woźniak, Marta; Michalak, Barbara; Wyszomierska, Joanna; Dudek, Marta K.; Kiss, Anna K. (Frontiers in Pharmacology, 2018)
Aim of the study: The aim of the present study was to investigate the effects of phytochemically characterized extracts connected with the traditional use (infusions and ethanolic extracts) of different parts of Syringa vulgaris (common lilac) on the pro- and anti-inflammatory functions of neutrophils. Active compounds were isolated from the most promising extract(s) using bioassay-guided fractionation, and their activity and molecular mechanisms of action were determined. Methods: The extracts were characterized using a HPLC-DAD- MSn method. The effects on ROS, MMP-9, TNF-α, IL-8 and MCP-1 production by neutrophils were measured using luminol-dependent chemiluminescence and enzyme-linked immunosorbent assay (ELISA) methods. The effects on p38MAPK, ERK1/2, JNK phosphorylation and NF-kB p65 translocation were determined using western blots. Results: The major compounds detected in the extracts and infusions belong to structural groups, including caffeic acid derivatives, flavonoids and iridoids. All extracts and infusions were able to significantly reduce ROS and IL-8 production. Bioassay-guided fractionation led to the isolation of the following secoiridoids: 2’’-epiframeroside, oleonuezhenide, oleuropein, ligstroside, neooleuropein, hydroxyframoside, and framoside. Neooleuropein appeared to be the most active compound in the inhibition of cytokine production by attenuating the MAP kinase pathways. Conclusion: The present study demonstrated that common lilac, which is a traditionally used medicinal plant in Europe, is a valuable source of active compounds, especially neooleuropein.